HUBUNGAN TINGKAT STRES DENGAN KUALITAS TIDUR PADA LANSIA DI WILAYAH KERJA UPTD PUSKESMAS SEI LEKOP KAB. BINTAN - Rama Yunita; Utari Christya Wardhani; Mira Agusthia (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Elderly is an individual who changes a lot both physically and mentally, especially the reduction in the various functions and abilities he once had. Nowadays there are many problems that tend to occur in the elderly both physically and psychologically, one of which is insomnia. Most of the elderly who suffer from stress experience sleep disturbances. This study aims to determine the relationship between stress levels and sleep quality in the elderly in the UPTD Work Area of the Sei Lekop Health Center, Kab. Bintan in 2022. The design of this study is a type of correlation research with a cross-sectional approach. The sample in this study were 85 elderly people and analyzed using the chi square test. The results of the study show that there is a relationship between stress levels and sleep quality in the elderly in the UPTD Work Area of the Sei Lekop Health Center, Kab. Bintan Year 2022 (p-value 0.000). It can be concluded that there is a relationship between stress levels and sleep quality in the elderly in the UPTD Work Area of the Sei Lekop Health Center, Kab. Bintan Year 2022. It is recommended for the elderly to be able to manage sleep well and avoid risk factors for sleep quality disturbances such as stress.